AAV9-mediated telomerase activation does not accelerate tumorigenesis in the context of oncogenic K-Ras-induced lung cancer. - Miguel A Muñoz-Lorente (PLoS Genetics, 2018)
Short and dysfunctional telomeres are sufficient to induce a persistent DNA damage response at chromosome ends, which leads to the induction of senescence and/or apoptosis and to various age-related conditions, including a group of diseases known as "telomere syndromes", which are provoked by extremely short telomeres owing to germline mutations in telomere genes. This opens the possibility of using telomerase activation as a potential therapeutic strategy to rescue short telomeres both in telomere syndromes and in age-related diseases, in this manner maintaining tissue homeostasis and ameliorating these diseases. In the past, we generated adeno-associated viral vectors carrying the telomerase gene (AAV9-Tert) and shown their therapeutic efficacy in mouse models of cardiac infarct, aplastic anemia, and pulmonary fibrosis. Although we did not observe increased cancer incidence as a consequence of Tert overexpression in any of those models, here we set to test the safety of AAV9-mediated Tert overexpression in the context of a cancer prone mouse model, owing to expression of oncogenic K-ras. As control, we also treated mice with AAV9 vectors carrying a catalytically inactive form of Tert, known to inhibit endogenous telomerase activity. We found that overexpression of Tert does not accelerate the onset or progression of lung carcinomas, even when in the setting of a p53-null background. These findings indicate that telomerase activation by using AAV9-mediated Tert gene therapy has no detectable cancer-prone effects in the context of oncogene-induced mouse tumors.